Justification : an introduction - Schreiner, Thomas R. (Illinois Crossway, 2023)
"Justification is by faith alone through grace alone to the glory of God alone. Justification by faith is rooted in the history of the Church, in the Old Testament witness, in the teaching of Jesus, the writings of the apostle Paul, and the rest of the New Testament. This book shows the scriptural underpinnings of the doctrine and the theological implications as well"--
Includes bibliographical references and indexes.
Keywords: Justification (Christian theology); Justification (Christian theology) -- Biblical teaching